Do The English Lecturers Using Technology for Teaching Online Class? - Umar, Vebrianti; Nasrullah; Rosalina, Elsa; Ningsih, Rahma Pitria; Nor, Hidayah (Universitas Pendidikan Ganesha, 2023)
Technology is an essential thing to support the learning process. Its use makes the teachers and students more accessible in the learning process and creates a pleasant atmosphere in the class, particularly during this covid 19 pandemic. Practically, even though technology positively impacts learning, not all teachers have sufficient technical skills to operate the learning application of online teaching. Therefore this study aims to analyze the english lecturers using technology for teaching online class. This study is using qualitative with narrative design research. Data collection of using technology in online classes involving difficulty and its solutions are narrated based on two English lecturer’s experience. The subjectof this study is two English lecturers in for exploring their experiences of using technology for teaching online class during this crucial situation of covid 19. All the data is analyzed thematically by organizing it based on the questions of interview. The findings present the strengths and the weaknesses of technology in online learning, and the way of overcoming the problem of using technology.